First principle based computations to evaluate propane and butane detection capabilities of gold doped graphene based gas sensor devices - Maity Indranil; Bhanja Souvik (EPJ Web of Conferences)
The present study focuses on the performance of gold (Au) doped graphene sheet in the presence of liquefied petroleum gas (LPG) molecules viz. propane and butane using first principle-based calculations, and all the results were compared via investigating different electronic and molecular properties. The propane and butane adsorbed Au-doped graphene-based structures were optimized using Gaussian 09W and GaussView 6.0 software tools. In the current attempt, the following electronic and gas-sensing parameters were studied including FMO (Frontier Molecular Orbitals) i.e., HOMO (Highest Occupied Molecular Orbital)-LUMO (Lowest Unoccupied Molecular Orbital), MEP (Molecular Electrostatic Potential) map, Raman spectra, FTIR (Fourier Transform Infrared Spectroscopy), I-V characteristics, adsorption energy, and binding distance. The HOMO-LUMO gap was found to be larger in the case of propane-adsorbed Au-doped graphene. MEP study also helps to visualize the interaction site and the underlying electronic characteristics. Similarly, adsorption energies and binding distances were calculated and used as key parameters for comparing the gas sensing performance. It was observed that the adsorption energy of propane on Au-doped graphene sheet was 1.159 times higher than that of butane, which indicates better detection capabilities of the sensing material (Au-doped graphene) towards propane among the other constituents of the LPG molecules.